Use of CTLA4Ig for Induction of Mixed Chimerism and Renal Allograft Tolerance in Nonhuman Primates. Issue 12 (13th November 2014) - Yamada, Y.; Ochiai, T.; Boskovic, S.; Nadazdin, O.; Oura, T.; Schoenfeld, D.; Cappetta, K.; Smith, R.‐N.; Colvin, R. B.; Madsen, J. C.; Sachs, D. H.; Benichou, G.; et al.
<x xml:space="preserve">Abstract</x> We have previously reported successful induction of renal allograft tolerance via a mixed chimerism approach in nonhuman primates. In those studies, we found that costimulatory blockade with anti‐CD154 mAb was an effective adjunctive therapy for induction of renal allograft tolerance. However, since anti‐CD154 mAb is not clinically available, we have evaluated CTLA4Ig as an alternative agent for effecting costimulation blockade in this treatment protocol. Two CTLA4Igs, abatacept and belatacept, were substituted for anti‐CD154 mAb in the conditioning regimen (low dose total body irradiation, thymic irradiation, anti‐thymocyte globulin and a 1‐month posttransplant course of cyclosporine [CyA]). Three recipients treated with the abatacept regimen failed to develop comparable lymphoid chimerism to that achieved with anti‐CD154 mAb treatment and these recipients rejected their kidney allografts early. With the belatacept regimen, four of five recipients developed chimerism and three of these achieved long‐term renal allograft survival (>861, >796 and >378 days) without maintenance immunosuppression. Neither chimerism nor long‐term allograft survival were achieved in two recipients treated with the belatacept regimen but with a lower, subtherapeutic dose of CyA. This study indicates that CD28/B7 blockade with belatacept can provide a clinically applicable alternative to anti‐CD154 mAb for promoting chimerism and renal allograft tolerance.